Allogeneic MHC-matched T-cell receptor α/β-depleted bone marrow transplants in SHIV-infected, ART-suppressed Mauritian cynomolgus macaques - Weinfurter J.T. (2023)
Allogeneic hematopoietic stem cell transplants (allo-HSCTs) dramatically reduce HIV reservoirs in antiretroviral therapy (ART) suppressed individuals. However, the mechanism(s) responsible for these post-transplant viral reservoir declines are not fully understood. Therefore, we modeled allo-HSCT in ART-suppressed simian-human immunodeficiency virus (SHIV)-infected Mauritian cynomolgus macaques (MCMs) to illuminate factors contributing to transplant-induced viral reservoir decay. Thus, we infected four MCMs with CCR5-tropic SHIV162P3 and started them on ART 6–16 weeks post-infection (p.i.), maintaining continuous ART during myeloablative conditioning. To prevent graft-versus-host disease (GvHD), we transplanted allogeneic MHC-matched α/β T cell-depleted bone marrow cells and prophylactically treated the MCMs with cyclophosphamide and tacrolimus. The transplants produced ~ 85% whole blood donor chimerism without causing high-grade GvHD. Consequently, three MCMs had undetectable SHIV DNA in their blood post-transplant. However, SHIV-harboring cells persisted in various tissues, with detectable viral DNA in lymph nodes and tissues between 38 and 62 days post-transplant. Further, removing one MCM from ART at 63 days post-transplant resulted in SHIV rapidly rebounding within 7 days of treatment withdrawal. In conclusion, transplanting SHIV-infected MCMs with allogeneic MHC-matched α/β T cell-depleted bone marrow cells prevented high-grade GvHD and decreased SHIV-harboring cells in the blood post-transplant but did not eliminate viral reservoirs in tissues.